Digital dannelse for ældre Undervisning af ældre i it efter Digitaliseringsstrategien - Bagger, Christoffer (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
This article presents the result of observational studies and interviews conducted of two types of it-education aimed at the elderly. The purpose is to illuminate how the volunteers at these learning facilities approach the needs and wants that older adults may have following the Digitization Strategy of 2014. The approach is mainly based on participant observations and interviews. The major finding of this study is that the focus of the volunteers extends far beyond the instrumental demands put on older adults by the Digitization Strategy. The focus is instead on a long line of other skills, and the volunteers can be said to guide their users towards a type of digital bildung (da: “digital dannelse”). In this digital bildung, as opposed to the implicit demands of national strategies and much previous research, the priority is on a self-guided and interest-focused approach to the medium of the computer. Occasionally this also includes a conscious rejection of the specific services that citizens are required to use according to the Digitization Strategy.